Pengembangan Layanan Informasi Berbasis ILL (Inter Library Loan) di Lingkungan Perguruan Tinggi Negeri Kota Malang - Ach. Nizam Rifqi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research is a research model that specifically examines the development of information and library services along with the development of technology and information that develops in the community using ILL (Inter Library Loan). The research method uses descriptive qualitative in analyzing and reviewing an ILL concept which is implemented in MILL (Malang Inter Library Loan). Libraries along with the development of information technology which is increasingly massive in its existence in the community are required to meet their various complex needs and want fast (instant) things. ILL (Inter Library Loan) offers a solution to overcome the library's efforts in meeting the needs of these users. MILL (Malang Inter Library Loan) is present as an innovation by adopting ILL, especially in the city of Malang in an effort to meet the various needs of increasingly complex library users. The technical efforts and MILL procedural policies are tried to be applied in the Malang city state university library under the legal umbrella of FKP2TN cooperation by holding the principle of information disclosure through sharing various resources owned by the users of each library